RESEÑA : Magdaleno Alegría, Antonio. Los límites de las libertades de expresión e información en el Estado social y democrático de Derecho. Madrid : Congreso de los Diputados, 2006 - Serrano Maíllo, María Isabel (Teoría y Realidad Constitucional, 2007)
Freedom of expresion is, perhaps, the most importan right we have. It is configured as a fundamental and human right, but it isn´t absolut. It has some limits to protect other human rights. But this limitation has to be suitable and proportionate. This is the topic of this paper: freedom of expression and it limits.